Developing and Validating a Breast Cancer Screening Health Literacy Questionnaire Guided by Sørensen’s Integrated Model for Malaysian Adults - Johari Chan, Melissa; Nik Farid, Nik Daliana; Thangiah, Nithiah; Ismail, Muhd Zulfadli Hafiz; Abdul Rani, Fairuz; Fadzil, Siti Sarah; Selvasingam, Ruthashini R; Tan, Cia Vei (Malaysian Journal of Medical Sciences, 2026)
Background: Health literacy is essential for informed decision-making and cancer prevention. In Malaysia, limited health literacy contributes to delayed breast cancer diagnoses and poorer outcomes among disadvantaged populations. However, there is no validated instrument for assessing breast cancer screening health literacy. Accordingly, this study aimed to develop and validate such a questionnaire for Malaysian adults.Methods: A three-phase, multi-method design was employed. Phase One involved item generation through a systematic review, online surveys, expert validation and translation. Phase Two included cognitive debriefing and an analysis of test–retest reliability. Phase Three consisted of a cross-sectional survey of 779 adults (mean age 36.6 years; 66% female) attending clinics in Selangor and Johor. The scale was evaluated psychometrically with exploratory factor analysis, internal consistency and confirmatory factor analysis using covariance-based structural equation modelling.Results: The initial 66-item tool was refined to a questionnaire with 41 items in seven domains showing strong reliability (Cronbach’s α ≥ 0.93; corrected item–total correlations ≥ 0.71). Weighted kappa values indicated moderate to almost perfect agreement (> 0.41) for most items. Confirmatory factor analysis showed factor loadings of 0.75 to 0.92, average variance extracted > 0.50, composite reliability > 0.70, heterotrait–monotrait ratios < 0.90 and acceptable fit indices (χ²/df = 2.18, GFI = 0.85, AGFI = 0.83, CFI = 0.95, TLI = 0.95, RMSEA = 0.052).Conclusion: The validated 41-item Breast Cancer Screening Health Literacy Questionnaire is a reliable and culturally appropriate tool in Bahasa Malaysia that can be employed in clinical and community settings to identify literacy gaps, develop tailored health promotion strategies and strengthen early detection initiatives.